Patterns and Best Practices of Knowledge Sharing among Programmers on Stack Overflow: A Qualitative Study - Cakra Wirabuana; M. Mushlih Ridho; Dana Indra Sensuse; Imairi Eitiveni; Deden Sumirat Hidayat; Sofiyanti Indriasari (Faculty of Computer Science Universitas Indonesia, 2025)
This research explores knowledge-sharing patterns and best practices among programmers on the Stack Overflow platform. Using a qualitative approach, the study analyzes interviews with seven programmers to identify user behavior and contributions to knowledge sharing. The findings reveal that most users exhibit passive usage, seeking solutions without actively participating due to introverted tendencies, time constraints, and concerns about redundancy and confidentiality. However, Stack Overflow remains a valuable resource for problem-solving. Best practices identified include using multiple forums, ensuring detailed and clear questions, and encouraging active participation. These strategies can enhance the quality of shared knowledge and create a more comprehensive and reliable knowledge base for the programming community. The study also suggests that addressing psychological barriers and integrating knowledge-sharing activities into routine work processes can increase active participation. These insights are essential for improving user engagement and the overall effectiveness of online knowledge-sharing platforms.